Factors associated with condom use by female adolescents in Goiânia City - Vieira, Maria A.S.; Guimarães, Eleuse M.B.; Barbosa, Maria A.; Turchi, Marília D.; Alves, Maria de Fátima C.; Seixas, Mirian S.C.; Garcia, Mônica M.D.; Minamisava, Ruth (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction: the Sexually Transmitted Diseases (STD) are highly prevalent in the world, being a public health problem, especially in developing coun-tries. The consistent and correct use of the condom reduces the risk of HIV and other STD transmission. The most susceptible population to STD is consti-tuted by adolescents and youngsters, due to the practice of unprotected sexual intercourse. Objective: describe the prevalence of the use of male condomreported by female adolescents and identify the factors associated to the inconsistent use of condom reported by the female adolescents resident in a HealthSector (HS) of Goiânia-GO, in Brazil. Method: Population based sample was 914 females adolescents age 15 to 19 year old, randomly selectes from deHS. The data were collected through the means of confidential interview, conducted in the units of the Family Health Program, where the adolescents wereattended. Result: 60% of the adolescents started sexual activities precociously and 42.1% of them presented previous pregnancy. Conclusion:The preva-lence of inconsistent use of the condom was high and adolescents presents other sexual risk behavior.